2021
DOI: 10.1111/ina.12950
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effectiveness of desk dividers in reducing droplet and airborne virus transmission

Abstract: The utilization of physical dividers has been recommended as a practical approach to reducing the droplet and aerosol transmissions of the COVID‐19 virus (SARS‐CoV‐2). This study conducted a series of experiments using video recording with a high‐speed camera, particle image velocimetry (PIV) technique, and concentration measurements. The effectiveness of Perspex desk dividers impeding the transient transmission during coughing in five representative layouts was investigated. The results showed that the divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…during the pandemic. However, it is interesting that their seating choices, whether intentional or unintentional, correspond to the findings of a study investigating the effectiveness of various types of desk dividers on COVID-19 virus transmission [ 43 ].…”
Section: Discussionmentioning
confidence: 97%
“…during the pandemic. However, it is interesting that their seating choices, whether intentional or unintentional, correspond to the findings of a study investigating the effectiveness of various types of desk dividers on COVID-19 virus transmission [ 43 ].…”
Section: Discussionmentioning
confidence: 97%
“…Cough machines also use pressurized air or mechanical systems to produce a spray modeled as cough, sneeze or speech droplets. Several studies have employed them to investigate the lifetime and dispersion of expectorated viral droplets into the air (Bartels et al 2022 ; Doremalen et al 2020 ; Li et al 2022b ; Lordly et al 2022 ). Aerosol-generating techniques provide the flexibility of producing desired droplet size ranges and controlling the injection velocity and other parameters.…”
Section: Experimental Methods To Analyze Droplet Transportmentioning
confidence: 99%
“…Setting up screens, partitions, and other physical isolation devices to divide the space into different areas to reduce direct respiratory contact between personnel changes the transmission path of pollutants, thus achieving a reduction in infections. For example, Li et al [16] used particle image velocimetry to monitor particle concentrations and a high-speed camera to record the effects of droplet transmission under different desktop partition placement measures and showed that using staggered configurations of desk partitions between infected and susceptible individuals can minimize droplet exposure. Mirzaie et al [17] derived an average droplet concentration of up to 3.80 × 10 −8 kg/m 3 nearest to the infected person at a wind speed of 7 m/s using computational fluid dynamics (CFD) techniques, verifying that installing barriers in front of personal seats can prevent infection to some extent.…”
Section: Introductionmentioning
confidence: 99%